Embodied Relating and Transformation - Sharpe, Hillary. author. aut Link
VIII, 136 p.
Keywords: "What kinds of embodied and relational learning can come from developing a responsive relationship with a horse? What insights might such ways of learning offer counselors and educators? In this book, the authors explore how women challenged by disordered eating develop transformative relational and embodied experiences through Equine-Facilitated Counseling (EFC). Embodiment refers to how we engage with others and the world in often habitual and taken for granted ways that shape who we are and the relationships we have. These habitual ways of being provide us with a sense of stability, but they can sometimes become constraining and problematic (as in the case of eating disorders). Our corporeal engagement with the world structures such habits, but it can also afford us opportunities to experiment, modify, and challenge problematic patterns, and in some instances, create new and preferred ones. The horses that participate in EFC present a vastly different sort of other who can help clients interrupt their sedimented ways of being and foster moments of responsivity that hold the power to become transformative. This theoretical context presents a different way of thinking about and practicing counseling – one that adds to a growing language of embodiment across a variety of disciplines. Chapters set forth a theoretical context for understanding the following: relationally embodied processes of stability and change, EFC, client stories from our research associated with riding horses in EFC, and implications we see for practice across different healing and learning contexts. ".